Prospective study of proton beam radiation therapy for adjuvant and definitive treatment of thymoma and thymic carcinoma: Early response and toxicity assessment. Issue 3 (March 2016) - Vogel, Jennifer; Berman, Abigail T.; Lin, Liyong; Pechet, Taine T.; Levin, William P.; Gabriel, Peter; Khella, Sami L.; Singhal, Sunil; Kucharczuk, John K.; Simone, Charles B.
Abstract: Background and purpose: Radiation is an important modality in treatment of thymic tumors. However, toxicity may reduce its overall benefit. We hypothesized that double-scattering proton beam therapy (DS-PT) can achieve excellent local control with limited toxicity in patients with thymic malignancies. Methods and materials: Patients with thymoma or thymic carcinoma treated with DS-PT between 2011 and 2015 were prospectively analyzed for toxicity and patterns of failure on an IRB-approved study. Results: Twenty-seven consecutive patients were evaluated. Patients were a median of 56 years and had thymoma (85%). They were treated with definitive (22%), salvage (15%) or adjuvant (63%) DS-PT to a median of 61.2/1.8 Gy [CGE]. No patient experienced grade ⩾3 toxicity. Acute grade 2 toxicities included dermatitis (37%), fatigue (11%), esophagitis (7%), and pneumonitis (4%). Late grade 2 toxicity was limited to a single patient with chronic dyspnea. At a median follow-up of 2 years, 100% local control was achieved. Three-year regional control, distant control, and overall survival rates were 96% (95% CI 76–99%), 74% (95% CI 41–90%), and 94% (95% CI 63–99%), respectively. Conclusions: This is the first cohort and prospective series of proton therapy to treat thymic tumors, demonstrating low rates of early toxicity and excellent initial outcomes.